World travel atlas 1997-1998 - Taylor, Mike (England : Columbus Press, 1997)
An atlas designed speciafically for the world traveler, containing maps on climate, time, health, driving, airports, international flight times and cruising.
Includes index.
Keywords: Travel -- Guidebooks; Atlases